2021
DOI: 10.1088/1361-6463/abfce5
|View full text |Cite
|
Sign up to set email alerts
|

A review of next generation bifacial solar farms: predictive modeling of energy yield, economics, and reliability

Abstract: Photovoltaic (PV) cell technology has made great progress over the past few decades, bringing the PV energy cost down to a point where it is competitive to conventional electricity prices. While monofacial panels have historically dominated the market, recent developments in the manufacturing of bifacial panels (collecting light from both faces) have made them accessible for commercial applications. It is therefore imperative to define the design principles so that the steeply expanding market of bifacial modu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(10 citation statements)
references
References 65 publications
0
10
0
Order By: Relevance
“…For example, the manufacturing and construction of bifacial PV (light collected from both sides of the panel surface) is driven by estimates of 20–40% electricity gains over monofacial panels, which could ostensibly drive smaller power plant footprints to meet finite electricity needs. However, the exponential increases in electricity demand globally and the nascent state of the technology’s economic and reliability outcomes mean that impacts on real-world LUIE are yet to be determined [ 79 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, the manufacturing and construction of bifacial PV (light collected from both sides of the panel surface) is driven by estimates of 20–40% electricity gains over monofacial panels, which could ostensibly drive smaller power plant footprints to meet finite electricity needs. However, the exponential increases in electricity demand globally and the nascent state of the technology’s economic and reliability outcomes mean that impacts on real-world LUIE are yet to be determined [ 79 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lazaroiu et al [15] studied the power generation gain and energy consumption of a photovoltaic system with solar tracking, and the results indicated a significant growth in the power production during morning and evening. Patel et al [21] showed that when the geographic latitude was lower than 30 • , the annual power generation of a single-axis tracking system was higher than that of an optimal fixed-tilt mounted system by 25-45%. Regarding the solar tracking method, based on the traditional maximum power point tracking method (MPPT) [22], Clifford and Eastwood [23] proposed a novel passive solar tracker, whose power generation gain could reach 30%.…”
Section: Introductionmentioning
confidence: 99%
“…28 The market share of tracking system is on the rise because it has the ability to enhance the energy yield at a lower cost. 24 The solar trackers are in charge of keeping the surface of the PV modules nearly perpendicular to direct irradiance almost all of the time, allowing them to collect a greater amount of irradiance. 29 Single-axis tracking and dual-axis tracking are the two main categories of solar tracking systems.…”
Section: Introductionmentioning
confidence: 99%